Tehnične zahteve kakovostnega ultrazvočnega aparata - Rainer, Saša (Radiology and oncology (Ljubljana), 1999)
Due to constant development and advances in ultrasound technology, criteria regarding the quality of ultrasound system are changing. Recent ultrasound system are based on digital technology. For imaging of the breast, high-frequency linear array transducers (5- to 12 MHz) are required; multifrequency probes are preferred. Basic equipment should include also convex array and sector (phased array) probes (3- to 5 MHz). All transducers should enable Doppler function. Reliable needle-guide is essential for US-guided biopsies and other procedures. System should support spectral (pulsed) Doppler, Color Doppler and Power (Angio) Doppler function and should enable detection of low-velocity flow. Dynamic range of the system should be as large as possible. Large internal memory is very useful. Most frequently used settings should be stored and easily recalled as preset function. System must be equipped with high-resolution color monitor. Color panel should be designed ergonomically. Options for image documentation are listed. System should enable integration into computer networks (Dicom 3,0 compatibility).
Keywords: diagnostika; Instrumentation; kvaliteta; medicinski aparati; Ultrasonography; ultrazvok